Text-based approach to teach English diphthongs - Katharina Rustipa; Agnes Widyaningrum; Teguh Kasprabowo; Yulistiyanti Yulistiyanti (EduLite: Journal of English Education, Literature and Culture, 2022)
Spoken communication demands the students' intelligible pronunciation of English speech sounds since unintelligible pronunciation hampers successful communication. However, the pronunciation of English speech sounds is problematic for many EFL learners even after years of learning English. The pronunciation problem is more complex when the speech sounds occur in a text. This is because, in an English class, the focus of pronunciation practice is usually on isolated words, phrases and sentences. Thus, they find difficulties when they apply the words, phrases, and sentences in a text. This study focused on teaching English diphthongs using the text-based approach. It investigated how text-based teaching can enhance the EFL students’ mastery to pronounce English diphthongs in a text. This study is an experimental design, comparing two groups of students’ pronunciation competence taught with genre/text-based approach and conventional approach. The research results revealed the effectiveness of text-based teaching since there was a significant difference in the students' competence taught with text-based teaching compared to those taught with the conventional method. Drilling techniques which were also applied played a vital role in the pronunciation practice. Based on the conclusion above, it is recommended that English teachers apply the text-based approach and drilling techniques as an alternative strategy to teach English diphthongs.